In-silico investigations of selective miRNA-gene targets and their validation studies in obstructive sleep apnea (OSA) patient cohorts. (August 2020) - Khurana, Sartaj; Waidha, Kamran; Guleria, Randeep; Sharda, Shivani; Bose, Sudeep
Graphical abstract: This model represents the profiling of miR-27 and let-7 and their targets in PBMC's derived from patients with obstructive sleep apnea. Highlights: Downregulation of miR-27 and let-7 in OSA. Prediction of miRNA secondary structures. Molecular docking of miRNA and their target genes. CNR1 and CRY2 are better targets for miR-27 and let-7 respectively. Differential expression of miRNA target genes in OSA compared to healthy. Abstract: Background: Obstructive sleep apnoea (OSA) is a prevalent form of sleep disordered breathing which results in sleep fragmentation and deprivation. Obesity and cardiovascular disorders are the major risk factors associated with OSA. Molecular analysis of the factors associated with OSA could demarcate the clinical analysis pattern in a population. Objective: This study pertains to in-silico analyses of miRNA and their gene targets with validation for their potential role in OSA as putative biomarker candidates. Methods: miRDB, TargetScan and miRanda databases were used to identify targets of miR-27 and let-7 that have documented role in OSA and co-related obesity and cardiovascular disorders. Quantitative PCR was used to analyze expression pattern of miR-27 and let-7 in obese and non-obese OSA patient cohorts with respective controls. In-silico analysis was done using PatchDoc to obtain atomic contact energy (ACE) scores that indicated the docked gene targets to the predicted miRNA structures. The docked structures were analysed using Maestro Suite 11 for the hydrogen and aromatic interactions. Results: Downregulation of miR-27 and let-7 in OSA compared to controls was observed. In-silico data analysis was performed for gene targets (TGFBR1, TGFBR2, SMAD2, SMAD4, CRY2 and CNR1) of the selected miRNAs (miR-27 and let-7). Among all, CNR1 and CRY2 were found to be better targets for miR-27 and let-7 respectively as per ACE scores, ROC scores and expression fold change in OSA. Conclusion: Our study gives insights to the expression profiling of miR-27 and let-7 and explore a set of potential target genes (CNR1 and CRY2) of these two miRNAs for a promising clinical relevance in OSA.